2011
DOI: 10.1007/s00101-011-1931-y
|View full text |Cite
|
Sign up to set email alerts
|

Anästhesiologisches Management der Sectio caesarea

Abstract: Currently the predominant anesthetic technique of choice in Germany is spinal anaesthesia and at a much higher rate than in 2002. In addition 12% of departments use traumatic Quincke needles which are associated with a higher incidence of postpuncture headache. Nitrous oxide is no longer frequently used in Germany. Finally, the administration of an antibiotic before cord clamping has been shown to lead to lower rates of endometritis and postoperative wound infection without detrimental effects on the newborn. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
0
19
1
5
Order By: Relevance
“…Withdrawing from the use of intrathecal morphine could be discussed in context of other large studies that report usage of intrathecal opioids in obstetrics 5 - 7 .…”
mentioning
confidence: 99%
“…Withdrawing from the use of intrathecal morphine could be discussed in context of other large studies that report usage of intrathecal opioids in obstetrics 5 - 7 .…”
mentioning
confidence: 99%
“…16,17 Considering the global situation, there is an increase in the use of regional anaesthesia techniques in Germany after 2002, and it has been reported that the most frequently used anaesthetic method in caesarean section surgeries is SA with a 90.8% usage rate. 18 In Spain, the usage rate of regional anaesthesia in caesarean sections is 98%, and among them the usage rate of SA is 75%. 19 In our study, the use of RA in CS was 90.76% and both in elective and emergency cases mostly RA was used.…”
Section: Discussionmentioning
confidence: 99%
“…If morphine is not used as intrathecal adjunct, like e.g. in Germany [18], a TAP block may be of potential benefit in this setting.…”
Section: Discussionmentioning
confidence: 99%